Constraining branon dark matter from observations of the Segue 1 dwarf spheroidal galaxy with the MAGIC telescopes. Issue 5 (1st May 2022) - Miener, T.; Nieto, D.; Gammaldi, V.; Kerszberg, D.; Rico, J.
Abstract: We present the first search for signatures of brane-world extra-dimensional dark matter (DM) in the very-high-energy gamma-ray band by scrutinizing observations of the dwarf spheroidal galaxy Segue 1 with the Major Atmospheric Gamma Imaging Cherenkov (MAGIC) telescope system. Branons are new degrees of freedom that appear within flexible brane-world models: they are weakly interacting massive particles and natural DM candidates. The ground-based gamma-ray telescopes MAGIC could indirectly detect branon DM in the multi-TeV mass range by observing secondary products of DM annihilation into Standard Model particles. In the absence of a signal, we place constraints on the branon DM parameter space by using a binned likelihood analysis of almost 160-hours deep exposure on the Segue 1 dwarf spheroidal galaxy by the MAGIC telescopes. Our most stringent limit to the thermally-averaged annihilation cross-section (at 95% confidence level) corresponds to 〈 σv 〉 ≃ 1.4 × 10 -23 cm 3 s -1 at a branon mass of ∼ 0.7 TeV.